HUBUNGAN ANTARA KADAR KOLESTEROL TOTAL DENGAN KADAR HIGH SENSITIVITY C-REACTIVE PROTEIN (HS-CRP) PADA PENDERITA DIABETES MELLITUS TIPE 2 - Gani Pratiwi (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2022)
Type 2 Diabetes Mellitus patients can cause oxidative stress which can trigger complications, namely cardiovascular disease. Increased levels of total cholesterol can cause atherosclerosis which can cause blockage of blood vessels so that it becomes one of the causes of cardiovascular disease. Atherosclerosis can cause inflammation and tissue damage so that the result of this inflammation causes an increase in levels of High sensitivity C-Reactive Protein (Hs-CRP). High sensitivity C-Reactive Protein (Hs-CRP) can be called the most significant predictor of inflammation markers of the risk of cardiovascular events. The purpose of this study was to determine the correlation between total cholesterol levels and levels of High sensitivity C Reactive Protein (Hs-CRP) in patients with Type 2 Diabetes Mellitus. This type of research was an analytical observation using a cross sectional approach. The results of statistical analysis using a non-parametric spearman rank test from the correlation test, the significance value of 24 samples was 0.392, then p0.05 the Correlation Coefficient was -0.183, which means that there is no correlation between total cholesterol levels and Hs-CRP levels in people with diabetes mellitus type 2 which is weakly correlated.